PENYESUAIAN DIRI ANAK JALANAN DI RUMAH PINTAR BANGJO KOTA LAMA KOTA SEMARANG - Muhammad Ilham Nur Saputra; Rusmana, Aep; Susanto, Eri (Pekerjaan Sosial, 2026)
Self-adjustment is an individual’s psychological ability to respond to environmental demands-both internal and external-in a healthy and constructive manner to create balance in social interactions. This study aims to provide insights into: (1) the characteristics of the respondents, (2) emotional maturity, (3) intellectual maturity, (4) social maturity, and (5) responsibility aspects of street children at Rumah Pintar Bangjo Semarang. This research used a quantitative approach with a survey method. The population consisted of 48 street children, with a sample of 32 selected through purposive sampling. Data collection techniques included questionnaires, observation, and documentation study. The instrument was developed based on Desmita’s (2019) theory and utilized a rating scale. Validity was assessed through expert judgment, and the reliability test using Cronbach’s Alpha yielded a result of 0.841 (> 0.7), indicating high reliability. The findings revealed that the self-adjustment level of street children was in the high category, with an average score of 86.71%. The emotional maturity aspect scored 82.60%, intellectual maturity 90.00%, social maturity 85.62%, and responsibility also showed a high score of 88.62%. The study found that the social and responsibility aspects still require reinforcement, particularly in dealing with environmental pressures and life demands. Therefore, the researcher proposes the MAS DITA (Self-Adjustment Program at Rumah Pintar Bangjo) intervention program using a group work approach-specifically the socialization group type-designed to comprehensively enhance the self-adjustment of street children at Rumah Pintar Bangjo Semarang.